Micropipette aspiration of porcine mesenchymal stem cells - Chang, Chui Rhong. (2013)
Mechanical behavior of stem cells can be studied with micropipette aspiration, in which the cells undergo a temporary deformation by being aspirated into a micro-glass tube while tracing the movement of the aspirated cell. In this project, we have investigated the stiffness of individual porcine mesenchymal stem cells (pMSCs) using micropipette aspiration technique together with elastic half-space model. Basic step-by-step procedures were noted down in the complete set-up of a micropipette system. Firstly, setting up and calibration of the system was done, followed by the learning of fabricating and scoring of micropipettes for aspiration and then the actual experimental testing. The experimental testing has to be conducted within the time-frame of 1hr each time. Each cell tested was conducted for 300seconds. Most of the pMSCs behave as viscoelastic solid with a initial increase in aspiration length and which gradually stabilizes with time. Besides that, other types of non-typical viscoelastic behavior of pMSCs were also seen. After comparing with Liao Kin et al[1] reported human mesenchymal stem cells (hMSCs), porcine mesenchymal stem cells are viscoelastic solid and it is also reported to be slightly stiffer than hMSCs.